2018
DOI: 10.1016/j.athoracsur.2018.02.087
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Nodal Metastases for Clinical T2N0 Esophageal Adenocarcinoma

Abstract: EUS is inaccurate for staging of T2N0 esophageal adenocarcinoma and often fails to identify nodal involvement. Identification of vascular invasion on preoperative biopsy should be explored as a prognostic marker to select patients for induction therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
2
4
0
2
Order By: Relevance
“…In our series, LN involvement was associated with vascular invasion. Similarly, Barbetta et al observed that vascular invasion is an independent predicting factor of pathologic nodal involvement 37 . Moreover, we previously reported that CD31, a marker of angiogenesis, was associated with nodal metastasis in EAC 38 .…”
Section: Discussionsupporting
confidence: 61%
“…In our series, LN involvement was associated with vascular invasion. Similarly, Barbetta et al observed that vascular invasion is an independent predicting factor of pathologic nodal involvement 37 . Moreover, we previously reported that CD31, a marker of angiogenesis, was associated with nodal metastasis in EAC 38 .…”
Section: Discussionsupporting
confidence: 61%
“…This was more common in poorly differentiated tumors (5). This is supported by the literature, with other studies citing 25-55% of these patients upstaged, and 35% found to have positive lymph nodes (6,7). This is not an insignificant finding, as the finding of positive nodes in this patient group led to poor survival (41% at 5-year follow-up) (6).…”
supporting
confidence: 61%
“…EUS allows for evaluation of depth of invasion, regional nodes, and lymphovascular invasion. Lymphovascular invasion is an area of interest because it is the only independent predictor of the presence of nodal involvement in a study of tumor variables (odds ratio 5.24) (6). EUS accuracy for the detection of regional nodes stands at 80%, and at 74-90% for the evaluation of T stage in all esophageal cancer patients, but the accuracy of T stage evaluation is lowest in T2 tumors, with accurate description of 31% (1).…”
Section: Stagingmentioning
confidence: 99%
“…The recent study "Predictors of Nodal Metastases for Clinical T2N0 EAC" by Barbetta and colleagues at MSKCC, NY, USA refutes the notion of EUS being the accurate modality for identification of the nodal involvement (13). In this novel study of 80 patients with clinically T2N0 EAC who were treated with surgery with or without adjuvant chemotherapy, preoperative staging by EUS was found to be inaccurate in 91% of the patients.…”
Section: Editorial Ct2n0 Esophageal Adenocarcinoma: Predictors Of Lymmentioning
confidence: 91%
“…Endoscopic resection as a diagnostic modality along with careful staging using a multitude of EUS, PET-CT, and elective thoracoscopic sampling may be employed to determine the patients who are candidates of an organ-preserving procedure. Barbetta and colleagues, through their study, have emphasized the need of identifying and stratifying such markers which may help avoid morbid resection in a select subset of patients (13). The study is a descriptive study, a retrospective review of the prospectively maintained database.…”
Section: Editorial Ct2n0 Esophageal Adenocarcinoma: Predictors Of Lymmentioning
confidence: 99%